Effect of Moisture Content Variation on Thermo-Physical Properties of Brown Variety Tigernut (Cyperus esculentus) - Usman, D. D.; Adanu, E. O.; Jahun, B. G.; Ibrahim, K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Knowledge of thermophysical properties is essential to the food processing industries. The properties are useful in modeling of thermal behavior of seeds during processing operations such as frying, baking, boiling fermentation and drying. To this end, the thermo physical properties (bulk density, porosity, surface area, thermal conductivity, thermal diffusivity and specific heat capacity) of brown variety tigernut (Cyperus esculentus) were investigated as a function of moisture content. In this study, thermal conductivity and specific heat capacity were determined by transient state heat transfer (line heat source) and mixture methods respectively, whereas, thermal diffusivity, bulk density, porosity and surface area were determined using formula methods. The evaluation was conducted at 5 moisture levels (20, 25, 30, 35 and 40% w.b) with 5 replications. The thermal conductivity and diffusivity increased from 0.03Wm-1k-1 to 0.13Wm-1k-1 and from 7.24 x 10-7m2s-1 to 11.06 x 10-7 m2s-1 as the moisture content increased from 20 to 40% respectively. The specific heat increased from 10.55 Jkg-1K-1 to 18.75 Jkg-1K-1, while the bulk density and surface area showed an increase from 421.40 kg/m3 to 639.80 kg/m3 and from 197.26 mm2 to 413.21 mm2 as moisture content increased. However, porosity decreased in value from 61.84 to 32.33% with an increase in moisture. Moisture content variation was statistically significant (p<0.05) on all properties. The obtained results will find use in the selection of suitable methods for processing of tigernut products, in a quality assessment of optimal modes of technological processes, and in the development of modern processing and handling equipment.